KUALITAS SANAD HADIST DALAM KITAB MIFTÂHUL JANNAH KARYA K.H.R AS’AD SYAMSUL ARIFIN SUKOREJO-SITUBONDO - Sofiah, Sofiah (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2018)
This study examines the quality of the hadith in the Miftahul Jannah by KHR. As'ad Syamsul Arifin. This book explains the rules of fiqh briefly. The majority of the fiqh chapters are not accompanied by hadith explanations, there are only four chapters accompanied by hadith, but their status is not included, so further studies are needed before believing and practicing the hadith. The focus of the study in this study is how the quality of the hadith sanad used by KHR As’ad Syamsul Arifin in the Miftahul Jannah book. The purpose of this study describes the quality of the hadith sanad used by Kyai As'ad Syamsul Arifin in the Miftahul Jannah book. The results of the study in the first hadith found that the sanad is weak (dhaif). The location of his weakness in the person of Abd Karim through the hadith narrated by al-Thabarani. But the hypocrisy of this hadith can be elevated to hasan lighairihi because there is a path of hadith narrated by Ibn Ady based on Abu Bakr al-Siddiq, and the path narrated by Ibn Abu Na'im from Ja'far b. Ishaq, who is both dhaif. Personally the narrator of the second hadith has a weak Sanad, in Abi al-Nadlr al-Abar who is not found his biography (majhul), but this hadith can be elevated to be hasan lighairihi because there are similar hadith narrated by al-Nasâ'i from the path Talhah and by Ibn Majah whose hadith is of value.